PENGARUH EARNINGS MANAGEMENT DAN ROA TERHADAP NILAI PERUSAHAAN DENGAN MODERASI CORPORATE GOVERNANCE - Eny Rufiyad Mawati, 13.05.52.0043; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2017)
The Company has long-term goal is to maximize shareholder wealth. Maximizing shareholder wealth can be reached by maximizing the firm value. The objective of the empirical study is to examine the effect of earnings management, ROA and corporate governance to the value of the firm, the role of corporate governance as a variable that moderates the effect of earnings management to the value of the firm, the role of corporate governance practices as a variable that moderates the effect of ROA to the value of the firm. The population of this research is companies that take the survey CGPI and listed in Indonesia Stock Exchange in 2012-2015. The sample collection technique has been done by using purposive sampling, and 52 sample companies sample during 4 years have been obtained. This research has been done by using multiple linear regressions analysis technique and by applying the interaction method. The result of this research shows that the earnings management does not have any influence to the firm value. ROA, corporate governance, and size has positive influence to the firm value. Corporate governance is not moderate variable the influence of earnings management to the firm value. Corporate governance is moderating variables influence ROA to the firm value.Keywords:Â Earnings Management, ROA, Corporate Governance, Size and Firm Value